Step
*
1
1
of Lemma
strong-continuity2-implies-3
1. [T] : Type
2. [F] : (ℕ ⟶ T) ⟶ ℕ
3. M : n:ℕ ⟶ (ℕn ⟶ T) ⟶ (ℕ?)
4. ∀f:ℕ ⟶ T. ((∃n:ℕ. ((M n f) = (inl (F f)) ∈ (ℕ?))) ∧ (∀n:ℕ. (M n f) = (inl (F f)) ∈ (ℕ?) supposing ↑isl(M n f)))
⊢ ∀f:ℕ ⟶ T
    ∃n:ℕ
     ((((λn,f. strong-continuity-test(M;n;f;M n f)) n f) = (inl (F f)) ∈ (ℕ?))
     ∧ (∀m:ℕ. ((↑isl((λn,f. strong-continuity-test(M;n;f;M n f)) m f)) 
⇒ (m = n ∈ ℕ))))
BY
{ (Reduce 0 THEN (D 0 THENA Auto) THEN (InstHyp [⌜f⌝] (-2)⋅ THENA Auto) THEN ExRepD THEN Thin (-5)) }
1
1. [T] : Type
2. [F] : (ℕ ⟶ T) ⟶ ℕ
3. M : n:ℕ ⟶ (ℕn ⟶ T) ⟶ (ℕ?)
4. f : ℕ ⟶ T
5. n : ℕ
6. (M n f) = (inl (F f)) ∈ (ℕ?)
7. ∀n:ℕ. (M n f) = (inl (F f)) ∈ (ℕ?) supposing ↑isl(M n f)
⊢ ∃n:ℕ
   ((strong-continuity-test(M;n;f;M n f) = (inl (F f)) ∈ (ℕ?))
   ∧ (∀m:ℕ. ((↑isl(strong-continuity-test(M;m;f;M m f))) 
⇒ (m = n ∈ ℕ))))
Latex:
Latex:
1.  [T]  :  Type
2.  [F]  :  (\mBbbN{}  {}\mrightarrow{}  T)  {}\mrightarrow{}  \mBbbN{}
3.  M  :  n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  T)  {}\mrightarrow{}  (\mBbbN{}?)
4.  \mforall{}f:\mBbbN{}  {}\mrightarrow{}  T
          ((\mexists{}n:\mBbbN{}.  ((M  n  f)  =  (inl  (F  f))))  \mwedge{}  (\mforall{}n:\mBbbN{}.  (M  n  f)  =  (inl  (F  f))  supposing  \muparrow{}isl(M  n  f)))
\mvdash{}  \mforall{}f:\mBbbN{}  {}\mrightarrow{}  T
        \mexists{}n:\mBbbN{}
          ((((\mlambda{}n,f.  strong-continuity-test(M;n;f;M  n  f))  n  f)  =  (inl  (F  f)))
          \mwedge{}  (\mforall{}m:\mBbbN{}.  ((\muparrow{}isl((\mlambda{}n,f.  strong-continuity-test(M;n;f;M  n  f))  m  f))  {}\mRightarrow{}  (m  =  n))))
By
Latex:
(Reduce  0  THEN  (D  0  THENA  Auto)  THEN  (InstHyp  [\mkleeneopen{}f\mkleeneclose{}]  (-2)\mcdot{}  THENA  Auto)  THEN  ExRepD  THEN  Thin  (-5))
Home
Index